Organizational compassion, person-organization fit and discretionary behaviours in non-governmental organizations: a moderated model - Kasekende, Francis; Nasiima, Sentrine; Byamukama, Rodgers (Emerald Publishing Limited, 2022)
The authors proposed that Organizational Compassion and Person-Organization-Fit dimensions interactively predict Discretionary Behaviours among employees in the Non-Governmental Organization (NGO) sector in Uganda. Design/methodology/approach – The authors employ structural equation modelling to test hypotheses. The research was carried out in two studies; the second one was done six months after the first study. Two samples of respondents were drawn from NGOs operating in West Nile and Kampala regions, respectively. Findings – Discretionary behaviours were significantly related to the cross-sectionally assessed predictors including organizational compassion and supplementary fit. Complementary fit did not significantly predict discretionary behaviours. Both supplementary fit and complementary fit moderated the association between organizational compassion and employee discretionary behaviours among both rural and urban setting placed NGOs. Practical implications – In order to boost employee exhibition of discretionary behaviours, leaders of NGOs should always endeavour to find viable organizational compassion-supplementary fit and organizational compassion-complementary fit blend that can add value to NGOs in Uganda. Originality/value – This is one of the few studies that have focused on testing the interaction effects of organizational compassion and person organization fit dimensions on discretionary behaviours. These results highlight both supplementary fit and complementary fit as key individual resources that promote the effects of organization compassion on discretionary behaviours among NGO workers in Uganda.
Keywords: Interaction effect; Organizational compassion; Person-organization fit; Discretionary behaviours; Non-governmental organizations (NGOs)